IMPLEMENTATION OF PHYSIC E-LEARNING USING FACEBOOK TO FACILITATE STUDENT’S CRITICAL THINKING SKILLS - Zainudin Zainudin (Lensa: Jurnal Kependidikan Fisika, 2016)
This study aims to describe the implementation of e-learning using social media facebook to practice critical thinking skills, the research subjects were 20 students of the first semester of school year 2014-2015 study program PGSD University of NU Surabaya (UNUSA), using a study design one group pre test-post test design. The data obtained were analyzed descriptive statistics. Aplication SAP can be implemented very well with the average percentage of 88.4% keterlaksanaan SAP. Critical thinking skills of students had increased the value of the pre-test and post test with the average for the indicator making skills hypotheses 65 to 86; indicators skills to analyze 55 to 83; indicators skills make conclusions 50 to 89. The response of students to the learning process of e-learning using social media FB showed that 100% of students enjoy participating in the learning process of e-learning, student learning assessment pleased with e-learning using social media FB 100%.  Based on the results, it can be concluded that that implementation of e-learning using social media FB can train students' critical thinking skills.